Impact of the microbiome on skin health - assessing the potential of probiotics in the treatment of rosacea - Skórska , Gabriela; Gunia, Katarzyna; Lecnar, Aleksandra; Szklarek, Ewa; Matras, Oliwia; Grylowska, Gabriela; Paluch, Anna; Palak, Andrzej; Rebizant, Marcin; Tryba, Michał (Quality in Sport, 2026)
Background: Rosacea is a chronic inflammatory dermatosis characterized by flushing, persistent erythema, telangiectasia, papules, and pustules affecting the facial skin. Increasing evidence suggests that disturbances in the skin and gut microbiota may contribute to disease pathogenesis through the gut–skin axis. Aim: This study aimed to review current knowledge regarding the role of the microbiome in rosacea pathogenesis and the potential therapeutic significance of probiotics. Materials and Methods: A narrative literature review was conducted using the PubMed, Cochrane Library, and Google Scholar databases. The following keywords were used: microbiome, rosacea, probiotics, and gut–skin axis. After screening and removal of duplicates, 122 publications were included, comprising original studies, review articles, case reports, and clinical guidelines. Results: Available evidence indicates a significant association between rosacea and dysbiosis of the skin and gut microbiota. Microbial alterations may contribute to immune dysregulation, epithelial barrier dysfunction, and activation of inflammatory pathways. Microorganisms such as Demodex folliculorum, Bacillus oleronius, Staphylococcus epidermidis, and Helicobacter pylori appear particularly relevant. Probiotic supplementation may improve barrier integrity, reduce inflammation, and enhance standard rosacea therapy. Conclusions: Modulation of the microbiome with probiotics may represent a promising adjunctive strategy in rosacea treatment; however, further clinical studies are required to establish evidence-based recommendations. Keywords gut microbiome, gut dysbiosis, rosacea, probiotics, skin-gut axis